2016
DOI: 10.1186/s13104-016-2112-5
|View full text |Cite
|
Sign up to set email alerts
|

A study on blood product usage and wastage at the public hospital, Guyana

Abstract: BackgroundBlood is a valuable resource and blood wastage in a low socio economic country could impose a very serious impact on healthcare. This study therefore analyzes the usage and wastage of blood and blood products at the Georgetown Public Hospital Cooperation (GPHC), Guyana.MethodsA retrospective study was conducted on the data retrieved from laboratory blood banking information system on usage and wastage of blood products during the years 2012–2014 at the public hospital. The data were analyzed in MS Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 11 publications
2
16
2
2
Order By: Relevance
“…However, no entire blood units were recorded in the current study since nearly all the blood donated units were processed to blood components in order to meet the regional blood requirements, which is in line with the results of previous studies in this regard. 1,18,19 Additionally, O+ was found to be the most ordered blood type and the ICU department was ranked first as having the highest volume of blood product orders. Consistently, Karami et al concluded that most of the orders were from the ICU department.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no entire blood units were recorded in the current study since nearly all the blood donated units were processed to blood components in order to meet the regional blood requirements, which is in line with the results of previous studies in this regard. 1,18,19 Additionally, O+ was found to be the most ordered blood type and the ICU department was ranked first as having the highest volume of blood product orders. Consistently, Karami et al concluded that most of the orders were from the ICU department.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include impaired blood bags, expired units, long-term storing in unsuited ambient temperature, the formation of blood clots in bags, insufficient knowledge of physicians on the blood order requirements, a request for excessive blood supplies for the possible over bleeding during the surgeries, poor blood management policies, and the lack of knowledge. 1,5 The rate of blood wastage in hospitals of the United States is reported from 0.1% to 6.7%. 10 Further, cross-matched blood units for each surgery are typically much more than the requested units thus recording the ratio of cross-matched blood to the number of transfused blood (C/T) is essential in blood transfusion facilities.…”
mentioning
confidence: 99%
“…For example, if the Red Blood Cell units are out of their temperature storage for more than 30 minutes after shipping out, they cannot be reissue and this will lead to blood wastage. The reason for this is that once the RBC units are out of their controlled temperature storage, the blood components warms up and lead to proliferation of bacterium within that period [3]. Therefore, maintaining the medical supplies within their controlled temperature storage is very important.…”
Section: Introductionmentioning
confidence: 99%
“…Current wastage levels range from 1% to 5% in most countries but can be as high as 25% in other centres. 2,3 This is primarily due to time expiry as platelets have a shelf life of 5-7 days. Blood wastage in the setting of liver transplantation is yet to be reviewed, where there is a very high blood utilisation over a short time frame and a potential for a break in the cold chain resulting in significant wastage.…”
Section: Introductionmentioning
confidence: 99%